PERAN PERKEMBANGAN MORAL TERHADAP PERILAKU PROSOSIAL REMAJA - Fredericksen Victoranto Amseke; Marleny Purnamasary Panis (Universitas Muhammadiyah Lampung, 2020)
ABSTRACTThe purpose of this study was to determine the effect of moral development on prosocial behavior in students grade VIII in SMP Negeri